2016
DOI: 10.1109/tasc.2016.2623222
|View full text |Cite
|
Sign up to set email alerts
|

Interfilament Resistance at 77 K in Striated HTS Coated Conductors

Abstract: -Striating HTS coated conductor (CC) tapes into narrow filaments offers the possibility of reducing the tapes' magnetization losses without unreasonably decreasing their current-carrying capability. However, realizing well-separated striations presents technological challenges, especially if the number of filaments is large and/or if a thick layer of metallic stabilizer is present. In these situations, the filaments can be easily coupled and their effectiveness to reduce magnetization losses is strongly dimini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…The authors reported good agreement with modeling of multiple current paths using a chain network model showing a strong dependence on filamentization process parameters (laser striation and post-oxygenation), barrier resistances, i.e. the horizontal resistance through the filament stack, and a dominating substrate current path [109]. The latter finding also matches well with the results obtained in [120].…”
Section: Experimentally Obtained Coupling Time Constantssupporting
confidence: 76%
See 2 more Smart Citations
“…The authors reported good agreement with modeling of multiple current paths using a chain network model showing a strong dependence on filamentization process parameters (laser striation and post-oxygenation), barrier resistances, i.e. the horizontal resistance through the filament stack, and a dominating substrate current path [109]. The latter finding also matches well with the results obtained in [120].…”
Section: Experimentally Obtained Coupling Time Constantssupporting
confidence: 76%
“…It was reported by Yanagisawa in 2011 [66] that magnet coils with a smaller tape width of REBCO-CC, a larger inner diameter and a higher ratio of operating current to the coil critical current generate a smaller central screening field ratio. For completeness, it is noted that for multifilamentary CCs in general, Q total = Q hysteresis + Q coupling + Q eddy [109]. Some of the first examinations of filamentized YBCO CCs were performed by Carr and Oberly in 1999.…”
Section: Hysteresis Loss and Filamentized Conductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the equivalent resistor model used in [4], [5], [8] and a resistivity of Hastelloy at 77 K of 1.24 µW.m [17] the barrier resistance, R b , was calculated. The barrier resistance was much greater than the Hastelloy, suggesting good separation, which should prevent significant coupling losses.…”
Section: F Interfilament Resistancementioning
confidence: 99%
“…It has been demonstrated that dividing the tape into n narrower filaments can reduce the hysteretic loss by a factor of n [1]- [3]. Additionally, coupling losses, due to resistive current flow between filaments, can be reduced by increasing the resistive barriers between superconducting regions and ensuring their transposition [4], [5].…”
Section: Introductionmentioning
confidence: 99%